Durasi Penggunaan Gadget dan Ketajaman Mata pada Remaja: Studi Korelasi: Duration of Gadget Use and Visual Acuity in Adolescents : a Correlation Study - Hanun, Istiqomi Saidah; Riyadi, Muskhab Eko (Poltekes Kemenkes Tanjungpinang, 2024)
Visual acuity issues frequently arise in teens and require care because of their significant impact on several parts of life, including learning. Adolescents may experience a decline in their visual acuity due to various circumstances, including exposure to light emitted by gadgets. The initial investigation revealed that some students exhibited a decrease in visual sharpness despite the infrequent use of gadgets. Conversely, some students reported normal visual sharpness despite frequent use of electronic gadgets. This phenomenon has interested researchers seeking to investigate the correlation between the amount of time teenagers spend using gadgets and their visual acuity. This study was observational and had a cross-sectional design. The population consisted of students from class X and XI who were pursuing a focus in Audio Video Engineering Expertise at SMK Muhammadiyah 3 Yogyakarta. The complete sampling technique was used to select 41 respondents for the sampling process. The measuring device utilized consisted of a questionnaire sheet to record the time of gadget usage, along with an eye acuity observation sheet employing the Snellen Chart. The statistical analysis used Kendall's Tau test. The findings indicated that a significant proportion of participants, specifically 35 individuals (85.4%), fell into the high-usage group for gadgets. Additionally, a majority of participants, specifically 25 individuals (61%), exhibited anomalies in their visual acuity. The statistical test yielded a p-value of 0.001 <0.05, indicating a significant association between the duration of gadget use and ocular acuity in adolescents. The correlation coefficient of 0.511 indicates a moderate relationship between these two variables. Adolescents should decrease their time using electronic devices to lower the likelihood of experiencing a decline in visual sharpness.